2017
DOI: 10.4103/ijmy.ijmy_59_17
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of patients having extensively drug-resistant tuberculosis in Gujarat, India

Abstract: Treatment outcome of XDR TB patients is extremely poor with high mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
3
4
1
2
Order By: Relevance
“…This implies that XDR-TB patients with a baseline body weight of <40 kg were significantly more likely to die than those with a baseline body weight of ≥40 kg. Similar to our finding, the patients' low body weight/body mass index at baseline visit has been reported as a risk factor for poor treatment outcomes among XDR-TB (Kwon et al, 2008;Jacobson et al, 2010;Tang et al, 2013;Prajapati et al, 2017) and MDR-TB patients (Ahmad et al, 2015;Javaid et al, 2017;Khan et al, 2019) by studies conducted elsewhere. One of the reasons of poor systemic availability of oral anti-TB drugs is their poor absorption from gastrointestinal tract (GIT).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This implies that XDR-TB patients with a baseline body weight of <40 kg were significantly more likely to die than those with a baseline body weight of ≥40 kg. Similar to our finding, the patients' low body weight/body mass index at baseline visit has been reported as a risk factor for poor treatment outcomes among XDR-TB (Kwon et al, 2008;Jacobson et al, 2010;Tang et al, 2013;Prajapati et al, 2017) and MDR-TB patients (Ahmad et al, 2015;Javaid et al, 2017;Khan et al, 2019) by studies conducted elsewhere. One of the reasons of poor systemic availability of oral anti-TB drugs is their poor absorption from gastrointestinal tract (GIT).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, a total of 149 (36.9%) patients died. The mortality rate in our cohort was comparatively higher than the frequency of deaths observed among XDR-TB patients in Georgia (15.09%) (Frank et al, 2019), Estonia (17.54%) (Kliiman & Altraja, 2009) and Russia (23.61%) (Yunusbaeva et al, 2019), and lower than that observed in India (51.8%) (Prajapati et al, 2017) and South Africa (43 and 53%) (Pietersen et al, 2015;Yuengling et al, 2018). The relatively low mortality rate in the aforementioned studies could be due to the hiding of death by high LTUF rate ranging from 14.81 to 37.7% in these studies (Kliiman and Altraja, 2009;Frank et al, 2019;Yunusbaeva et al, 2019) as compared to 7.7% in our cohort.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Malheureusement, aucun test de sensibilité des autres médicaments de deuxième ligne n'était disponible, ce qui aurait pu entraîner une administration inutile de médicaments inefficaces. Cela nécessite la mise en place d'infrastructures et de laboratoires dotés des dernières technologies pour tester la sensibilité aux autres médicaments [16]. Chaque patient a été suivi mensuellement pour l'évaluation clinique (poids corporel), l'examen de la culture des expectorations, la radiographie thoracique, un bilan hématologique et biochimique systématique ainsi qu’un ECG en cas de prise de délamanide et la surveillance des effets indésirables jusqu'à achèvement de la durée du traitement.…”
Section: Discussionunclassified